PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KEUANGAN MELALUI PEMBERDAYAAN KARYAWAN DAN KUALITAS LAYANAN PADA PERUSAHAAN ASURANSI JIWA DI SURABAYA - Nindya Angelica Ganeswari Sutheja (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of leadership style to employee’s empowerment, leadership style to service quality, employee’s empowerment to financial performance, service quality to financial performance, employee’s empowerment to service quality, and leadership style to financial performance on life insurance firms in Surabaya. This study used quantitative approach, and the data were obtained through the distribution of questionnaires and financial report of life insurance firms in Surabaya. The samples used in this study were 30 life insurance firms in Surabaya listed on Book Directories of Insurance Otoritas Jasa Keuangan 2014, with each of 10 employees and 10 customers in each firm. The data obtained was processed by using SmartPLS software. This study showed that there were positive and significant relationship of leadership style to employee’s empowerment, leadership style to service quality, employee’s empowerment to financial performance, service quality to financial performance, employee’s empowerment to service quality, and leadership style to financial performance on life insurance firms in Surabaya.